Le site archéologique médiéval et moderne de Terravecchia (Sicile, Italie) - Philippe Racinet; George-Pierre Woimant (Archéologie Médiévale)
Archaeological and historical research carried out on the Sicilian village mentioned in texts as early as the 12th century, and abandoned following the 1693 earthquake, consisted in a complete field walking project including a morphological survey. This has enabled us to localise occupation concentrations on an uneven landscape, organized around particular poles, such as the castle or the churches. The survey, completed by surface cleaning of targeted areas, constitutes a reliable source for archaeological research. This took the form of isolated test areas aiming at throwing light on the origins of the town and its organization during the Post-medieval period. Systematic and planned modifications were brought to the urban form towards the end of the Middle Ages, implying major levelling and rebuilding phases, doubtlessly followed by a period of poorly controlled -if at all- intense urbanisation.